Bio-based branched sulfonated pbf-peg hydrophilic particles, methods of making, and aqueous slurries

CN122958686APending Publication Date: 2026-10-23HUIQIANG WUHAN NEW ENERGY MATERIAL TECH +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611077392.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]针对现有技术中PBF亲水性差、耐热性与离子电导性难以兼顾,以及隔膜涂覆材料环保性差、适配性不足等缺陷,本发明提供一种生物基支化磺化PBF-PEG亲水颗粒及其制备方法与水性浆料,实现高耐热、高亲水、高离子电导的协同,同时简化制备工艺、降低环境影响,适配高速涂覆需求

Benefits of technology

[0020]本发明借助核壳型支化嵌段结构设计的亲水颗粒,以聚呋喃二甲酸丁二醇酯作为核心,确保具备高耐热性,从而解决现有改性PBF耐热性降低的问题;在壳层引入磺化呋喃二甲酸亲水基团,并结合聚乙二醇-2000的亲水增韧效应,显著增强亲水性与离子电导率,达成高耐热性、高亲水性以及高离子电导率的协同效果,填补生物基PBF在水性隔膜涂覆领域的应用空白。同时,引入多元醇提供支化结构,稳定核壳结构,防止颗粒团聚,进一步提升力学性能与热稳定性;将S - FDCA的磺化度控制在0.8~1.2,兼顾亲水性能与结构稳定性,避免因过度磺化导致性能恶化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application provides a kind of bio-based branched sulfonated PBF-PEG hydrophilic particles and its preparation method and aqueous slurry, the hydrophilic particle is core-shell type branched block copolymer, with polybutylene furandicarboxylate as core, shell layer is composed of sulfonated furandicarboxylic acid, PEG-2000 block and branched structure provided by polyol, the preparation method of hydrophilic particle includes esterification, polycondensation and neutralization self-emulsifying three-step process, the core-shell structure is controlled by torque online monitoring and S-FDCA self-emulsifying characteristics.It is realized that the hydrophilic particle of the present application has high thermal stability, high ionic conductivity and self-emulsifying water dispersibility, and the obtained coated separator electrolyte contact angle is less than 30 °, which can significantly improve the safety and cycle performance of lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials and battery separator technology, specifically to a bio-based branched sulfonated PBF-PEG hydrophilic particle, its preparation method, and an aqueous slurry. Background Technology

[0002] With the rapid development of new energy vehicles and energy storage batteries, the performance requirements for battery separators are continuously increasing. They not only need to possess excellent thermal stability and mechanical properties, but also good hydrophilicity and ionic conductivity to ensure battery cycle life, fast-charging performance, and safety. Driven by global "dual carbon" goals, bio-based materials, with their renewable and environmentally friendly characteristics, are gradually replacing traditional petroleum-based materials and becoming a research focus.

[0003] Polybutylene furanate (PBF), a novel bio-based polyester material synthesized from bio-based furanyl dicarboxylic acid (FDCA) and 1,4-butanediol (BDO), possesses excellent thermal stability, mechanical properties, and biodegradability, demonstrating promising application potential in packaging, fibers, and other fields. However, pure PBF exhibits extremely poor hydrophilicity, lacking hydrophilic groups in its molecular chain, making it unsuitable for direct application in aqueous membrane coatings. Furthermore, when simply copolymerizing PBF (e.g., with polyethylene glycol (PEG), a trade-off arises between heat resistance and hydrophilicity / ionic conductivity—that is, while hydrophilicity increases, the thermal decomposition temperature decreases significantly, making it difficult to meet the safety requirements for battery separators used in high-temperature environments.

[0004] Currently, most battery separator coating materials use petroleum-based polymers (such as polyvinylidene fluoride (PVDF)). Their preparation process requires large amounts of organic solvents, causing environmental pollution and resulting in high costs and low coating efficiency. Existing bio-based separator coating materials generally suffer from drawbacks such as simple structures, uneven performance, and complex preparation processes. They struggle to achieve a synergistic effect of high heat resistance, high hydrophilicity, and high ionic conductivity, and there is a lack of suitable aqueous slurry systems for high-speed coating. These factors limit the large-scale application of bio-based materials in the battery separator field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, such as poor hydrophilicity of PBF, difficulty in simultaneously achieving both heat resistance and ionic conductivity, and poor environmental friendliness and insufficient adaptability of membrane coating materials, this invention provides a bio-based branched sulfonated PBF-PEG hydrophilic particle, its preparation method, and an aqueous slurry. This achieves a synergistic effect of high heat resistance, high hydrophilicity, and high ionic conductivity, while simplifying the preparation process, reducing environmental impact, and adapting to high-speed coating requirements.

[0006] The technical solution provided by this invention is: a bio-based branched sulfonated PBF-PEG hydrophilic particle, wherein the hydrophilic particle is a core-shell branched block copolymer with polybutylene furanate (PBF) as the core and the shell is composed of sulfonated furanate (S-FDCA), PEG-2000 blocks and a branched structure provided by polyol.

[0007] Furthermore, the hydrophilic particles possess high heat resistance, high ionic conductivity, and excellent hydrophilicity. The particle size of the hydrophilic particles is 90–150 nm, the glass transition temperature Tg is 30–40 °C, and the thermal decomposition temperature Td > 390 °C.

[0008] Furthermore, the polyol is at least one of glycerol and pentaerythritol.

[0009] Furthermore, the hydrophilic particles are made from the following bio-based raw materials in molar ratio: furanyl dicarboxylic acid (FDCA): sulfonated furanyl dicarboxylic acid (S-FDCA): 1,4-butanediol (BDO): PEG-2000: polyol = (8-9): (1-2): 10: (0.3-0.7): (0.1-0.3).

[0010] Furthermore, the sulfonated furandicarboxylic acid is at least one of para-sulfonated furandicarboxylic acid and meta-sulfonated furandicarboxylic acid, and its degree of sulfonation is 0.8 to 1.2.

[0011] Another technical solution provided by this invention: a method for preparing bio-based branched sulfonated PBF-PEG hydrophilic particles, comprising the following steps:

[0012] (1) Esterification reaction: Add furanyl dicarboxylic acid, sulfonated furanyl dicarboxylic acid, 1,4-butanediol, PEG-2000 and polyol according to the formula, and add 250-350 ppm of catalyst with the total mass of raw materials. Esterify at 180-200℃ under nitrogen atmosphere until the water output reaches 85-95% of the theoretical water output.

[0013] (2) Polycondensation reaction: Polycondensation is carried out at a vacuum degree <100 Pa and a temperature of 220~235℃ for 2.5~3.5 h until the torque is 50~80 N·m, and the polycondensation product is obtained;

[0014] (3) Neutralization and self-emulsification: Add 5%~8% NMP to the condensation product, add deionized water and triethylamine dropwise at 75~85℃ until the pH is 7.2~7.8, disperse at 8000~12000 r / min for 30~40 min, remove NMP to obtain a hydrophilic particulate emulsion with a solid content of 28%~32%.

[0015] Furthermore, the catalyst is at least one of tetrabutyl titanate and isopropyl titanate.

[0016] Another technical solution provided by the present invention is an aqueous slurry, which is mainly composed of the hydrophilic particles. The aqueous slurry is made from the following raw materials in parts by weight: 35-45 parts hydrophilic particle emulsion, 55-65 parts deionized water, 0.1-0.3 parts dispersant, 0.05-0.15 parts wetting agent, and 0.05-0.2 parts thickener.

[0017] Furthermore, the dispersant is selected from at least one of ammonium polyacrylate and sodium polycarboxylate; the wetting agent is selected from at least one of polyether-modified polysiloxane and acetylenic diol wetting agents; and the thickener is selected from at least one of HASE and HEUR.

[0018] Furthermore, the aqueous slurry is suitable for coating PE / PP base films, with a dry film thickness of 1~3μm, a viscosity of 20~40mPa·s, and is suitable for high-speed coating at 50~100 m / min.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] This invention utilizes hydrophilic particles with a core-shell branched block structure, using polybutylene furanate (PBF) as the core to ensure high heat resistance, thus solving the problem of reduced heat resistance in existing modified PBF. By introducing sulfonated furanate hydrophilic groups into the shell layer and combining this with the hydrophilic toughening effect of polyethylene glycol-2000, hydrophilicity and ionic conductivity are significantly enhanced, achieving a synergistic effect of high heat resistance, high hydrophilicity, and high ionic conductivity, filling the application gap of bio-based PBF in the field of aqueous membrane coating. Simultaneously, the introduction of polyols provides a branched structure, stabilizes the core-shell structure, prevents particle aggregation, and further improves mechanical properties and thermal stability. The degree of sulfonation of S-FDCA is controlled at 0.8~1.2, balancing hydrophilicity and structural stability, and avoiding performance deterioration due to excessive sulfonation.

[0021] This invention employs an integrated esterification-polymerization-neutralization self-emulsification preparation process, requiring no complex equipment. The process is simple and highly controllable, ensuring the integrity of the PBF backbone and the controllability of its branched structure through optimized reaction parameters. The self-emulsification process eliminates the need for additional emulsifiers, reducing costs. The resulting emulsion after NMP removal is environmentally friendly and pollution-free, meeting green production requirements. The aqueous membrane coating slurry formulation based on these hydrophilic particles is rationally formulated, with viscosity, solid content, and other parameters compatible with high-speed coating, resulting in high coating efficiency. It is also compatible with lithium-ion battery membranes, significantly improving the hydrophilicity, ionic conductivity, and thermal stability of the coated membrane, effectively extending battery cycle life, improving fast-charging performance, and enhancing safety. Furthermore, all raw materials are bio-based or environmentally friendly, reducing dependence on petroleum resources and aligning with "dual-carbon" goals and green development principles, demonstrating broad prospects for industrial application. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below with reference to specific embodiments. However, the following embodiments are only preferred embodiments of this invention and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0023] Example 1

[0024] A method for preparing an aqueous membrane coating slurry containing bio-based branched sulfonated PBF-PEG hydrophilic particles, the specific steps of which are as follows:

[0025] 1. Preparation of hydrophilic particles

[0026] (1) Esterification reaction: Add 0.85mol of FDCA, 0.15mol of S-FDCA, 1.00mol of BDO, 0.05mol of PEG-2000 and 0.02mol of glycerol by molar ratio, and add 300ppm of tetrabutyl titanate as a catalyst. Purge the air in the reaction system with nitrogen and control the temperature at 190℃ to carry out the esterification reaction. Stop the esterification when the amount of water produced reaches 90% of the theoretical amount of water produced.

[0027] (2) Polycondensation reaction: The esterification product is transferred to the polycondensation reactor, the vacuum degree is controlled to be <100 Pa, the temperature is 225℃, and the polycondensation reaction is carried out for 3.0h until the torque of the reaction system reaches 65 N·m. The polycondensation is stopped to obtain the branched sulfonated PBF-PEG copolymer.

[0028] (3) Neutralization and self-emulsification: Add 6.5% NMP by mass of the condensation product to the condensation product, stir to dissolve, control the temperature at 80℃, slowly add deionized water and TEA, adjust the pH of the system to 7.5, then disperse at 10000 r / min for 35 min, remove NMP by vacuum distillation to obtain a hydrophilic particulate emulsion with a solid content of 30%; the hydrophilic particles are core-shell type with a particle size of 120 nm, Tg of 35℃ and Td of 400℃; the S-FDCA is para-sulfonated furan dicarboxylic acid with a sulfonation degree of 1.0.

[0029] 2. Preparation of water-based diaphragm coating slurry

[0030] By mass fraction, take 40 parts of the above-mentioned 30% solid content hydrophilic particle emulsion, 60 parts of deionized water, 0.2 parts of ammonium polyacrylate dispersant, 0.1 parts of polyether-modified polysiloxane wetting agent, and 0.1 parts of HASE thickener, mix them evenly, and stir and disperse until there are no obvious particles in the system to obtain an aqueous membrane coating slurry; the viscosity of the slurry is 30 mPa·s, which is suitable for PE base film coating, with a dry film thickness of 2 μm, and is suitable for high-speed coating at 80 m / min.

[0031] Example 2

[0032] A method for preparing an aqueous membrane coating slurry containing bio-based branched sulfonated PBF-PEG hydrophilic particles, the specific steps of which are as follows:

[0033] 1. Preparation of hydrophilic particles

[0034] (1) Esterification reaction: Add 0.8 mol of FDCA, 0.20 mol of S-FDCA, 1.00 mol of BDO, 0.03 mol of PEG-2000 and 0.01 mol of pentaerythritol by molar ratio, and then add 250 ppm of isopropyl titanate as a catalyst. Purge the air in the reaction system with nitrogen and control the temperature at 180℃ to carry out the esterification reaction. Stop the esterification when the water output reaches 85% of the theoretical water output.

[0035] (2) Polycondensation reaction: The esterification product is transferred to the polycondensation reactor, the vacuum degree is controlled to be <100 Pa, the temperature is 220℃, and the polycondensation reaction is carried out for 3.5h until the torque of the reaction system reaches 50 N·m. The polycondensation is stopped to obtain the branched sulfonated PBF-PEG copolymer.

[0036] (3) Neutralization and self-emulsification: Add 5% NMP by mass of the condensation product to the condensation product, stir to dissolve, control the temperature at 75℃, slowly add deionized water and TEA, adjust the pH of the system to 7.2, then disperse at 8000 r / min for 40 min, remove NMP by vacuum distillation to obtain a hydrophilic particulate emulsion with a solid content of 28%; the hydrophilic particles are core-shell type with a particle size of 90 nm, Tg of 30℃ and Td of 395℃; the S-FDCA is meta-sulfonated furan dicarboxylic acid with a sulfonation degree of 0.8.

[0037] 2. Preparation of water-based diaphragm coating slurry

[0038] By mass fraction, take 35 parts of the above-mentioned 28% solid content hydrophilic particle emulsion, 65 parts of deionized water, 0.1 parts of sodium polycarboxylate dispersant, 0.05 parts of acetylenol wetting agent, and 0.05 parts of HEUR thickener, mix them evenly, and stir and disperse until there are no obvious particles in the system to obtain an aqueous membrane coating slurry; the viscosity of the slurry is 20 mPa·s, which is suitable for PP base film coating, with a dry film thickness of 1 μm, and is suitable for high-speed coating at 100 m / min.

[0039] Example 3

[0040] A method for preparing an aqueous membrane coating slurry containing bio-based branched sulfonated PBF-PEG hydrophilic particles, the specific steps of which are as follows:

[0041] 1. Preparation of hydrophilic particles

[0042] (1) Esterification reaction: Add 0.9 mol of FDCA, 0.10 mol of S-FDCA, 1.00 mol of BDO, 0.07 mol of PEG-2000 and 0.03 mol of glycerol by molar ratio, and add tetrabutyl titanate with a total monomer mass of 350 ppm as a catalyst. Purge the air in the reaction system with nitrogen and control the temperature at 200℃ to carry out the esterification reaction. Stop the esterification when the water output reaches 95% of the theoretical water output.

[0043] (2) Polycondensation reaction: The esterification product is transferred to the polycondensation reactor, the vacuum degree is controlled to be <100 Pa, the temperature is 235℃, and the polycondensation reaction is carried out for 2.5h until the torque of the reaction system reaches 80 N·m. The polycondensation is stopped to obtain the branched sulfonated PBF-PEG copolymer.

[0044] (3) Neutralization and self-emulsification: Add 8% NMP by mass of the condensation product to the condensation product, stir to dissolve, control the temperature at 85℃, slowly add deionized water and TEA, adjust the pH of the system to 7.8, and then disperse at 12000 r / min for 30 min. Remove NMP by vacuum distillation to obtain a hydrophilic particle emulsion with a solid content of 32%; the hydrophilic particles are core-shell type with a particle size of 150 nm, Tg of 40℃, and Td of 410℃; the S-FDCA is a mixture of para-sulfonated furanyl dicarboxylic acid and meta-sulfonated furanyl dicarboxylic acid (mass ratio 1:1) with a sulfonation degree of 1.2.

[0045] 2. Preparation of water-based diaphragm coating slurry

[0046] By mass fraction, take 45 parts of the above-mentioned 32% solid content hydrophilic particle emulsion, 55 parts of deionized water, 0.3 parts of ammonium polyacrylate dispersant, 0.15 parts of polyether modified polysiloxane wetting agent, and 0.2 parts of HEUR thickener, mix them evenly, and stir and disperse until there are no obvious particles in the system to obtain an aqueous membrane coating slurry; the viscosity of the slurry is 40 mPa·s, which is suitable for PE / PP composite base film coating, with a dry film thickness of 3μm, and is suitable for high-speed coating at 50 m / min.

[0047] Comparative Example 1 (without S-FDCA)

[0048] Following the method of Example 1, FDCA was increased to 1.00 mol, without adding S-FDCA, while the other proportions and processes remained unchanged. The esterification water yield reached the theoretical value of 92%, and the polycondensation torque reached 58 N·m. During neutralization and self-emulsification, the system exhibited a large precipitate suspension state, failing to form a stable emulsion, and completely separated after standing. This comparative example demonstrates that S-FDCA is the key component for achieving self-emulsification and dispersion of the product of this invention.

[0049] Comparative Example 2 (without PEG-2000)

[0050] Following the method of Example 1, without PEG-2000, the amount of BDO was increased accordingly to maintain the balance of total hydroxyl groups, while other proportions and processes remained unchanged. The esterification water yield reached 94% of the theoretical value, and the polycondensation torque reached 66 N·m. The particle size of the emulsion obtained from neutralization and self-emulsification was 165 nm, but the Tg increased to 54 °C. After coating, the diaphragm became more brittle, and coating cracks appeared during folding tests. The electrolyte contact angle, measured at 35°, remained at 42° after static testing, indicating a significant decrease in hydrophilicity and ion conductivity. This comparative example demonstrates that PEG-2000 is indispensable for adjusting the Tg to the target range and improving coating flexibility.

[0051] Performance testing

[0052] The hydrophilic particles prepared in Examples 1-3 and Comparative Examples 1-2 were tested according to industry-standard testing methods. The test results are shown in the table below:

[0053] Table 1 Performance Test Results

[0054]

[0055] Following industry-standard testing methods, the performance of the membranes coated with the aqueous slurries prepared in Examples 1-3 above was tested, and the test results are shown in the table below:

[0056]

[0057] The test results show that the hydrophilic particles prepared by this invention meet the requirements of particle size 90–150 nm, Tg 30–40 °C, and Td > 390 °C, and have both excellent hydrophilicity and ionic conductivity. The viscosity, dry film thickness and other parameters of the aqueous slurry are suitable for high-speed coating, and the coated separator has excellent performance and fully meets the requirements for battery separator use.

[0058] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A bio-based branched sulfonated PBF-PEG hydrophilic particle, characterized in that, The hydrophilic particles are core-shell branched block copolymers with polybutylene furanate (PBF) as the core and the shell composed of sulfonated furanate, PEG-2000 blocks, and branched structures provided by polyols.

2. The bio-based branched sulfonated PBF-PEG hydrophilic particles according to claim 1, characterized in that, The hydrophilic particles have high heat resistance, high ionic conductivity and excellent hydrophilicity. The particle size of the hydrophilic particles is 90–150 nm, the glass transition temperature Tg is 30–40 °C and the thermal decomposition temperature Td is >390 °C.

3. The bio-based branched sulfonated PBF-PEG hydrophilic particles according to claim 1, characterized in that, The polyol is at least one of glycerol and pentaerythritol.

4. The bio-based branched sulfonated PBF-PEG hydrophilic particles according to claim 1, characterized in that, The hydrophilic particles are made from the following bio-based raw materials in molar ratio: furanyl dicarboxylic acid: sulfonated furanyl dicarboxylic acid: 1,4-butanediol: PEG-2000: polyol = (8-9): (1-2): 10: (0.3-0.7): (0.1-0.3).

5. The bio-based branched sulfonated PBF-PEG hydrophilic particles according to claim 4, characterized in that, The sulfonated furanyl dicarboxylic acid is at least one of para-sulfonated furanyl dicarboxylic acid and meta-sulfonated furanyl dicarboxylic acid, and its degree of sulfonation is 0.8 to 1.

2.

6. The method for preparing hydrophilic particles according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Esterification reaction: Add furanyl dicarboxylic acid, sulfonated furanyl dicarboxylic acid, 1,4-butanediol, PEG-2000 and polyol according to the formula, and add a catalyst with a total mass of 250-350 ppm of bio-based raw materials. Esterify at 180-200℃ under nitrogen atmosphere until the effluent reaches 85-95% of the theoretical effluent. (2) Polycondensation reaction: Polycondensation is carried out at a vacuum degree <100 Pa and a temperature of 220~235℃ for 2.5~3.5 h until the torque is 50~80 N·m, and the polycondensation product is obtained; (3) Neutralization and self-emulsification: Add 5%~8% NMP by mass of the polycondensation product, add deionized water and triethylamine dropwise at 75~85℃ until the pH is 7.2~7.8, disperse at 8000~12000 r / min for 30~40 min, remove NMP to obtain a hydrophilic particulate emulsion with a solid content of 28%~32%.

7. The method for preparing hydrophilic particles according to claim 6, characterized in that, The catalyst is at least one of tetrabutyl titanate and isopropyl titanate.

8. An aqueous slurry, characterized in that, The aqueous slurry is made from the hydrophilic particles as described in any one of claims 1-5 as the main component, and the raw materials are prepared in the following parts by weight: 35-45 parts hydrophilic particle emulsion, 55-65 parts deionized water, 0.1-0.3 parts dispersant, 0.05-0.15 parts wetting agent, and 0.05-0.2 parts thickener.

9. The aqueous slurry according to claim 8, characterized in that, The dispersant is selected from at least one of ammonium polyacrylate and sodium polycarboxylate; the wetting agent is selected from at least one of polyether-modified polysiloxane and acetylenic diol wetting agents; and the thickener is selected from at least one of HASE and HEUR.

10. The aqueous slurry according to claim 8, characterized in that, The aqueous slurry is suitable for coating PE / PP base films, with a dry film thickness of 1~3μm, a viscosity of 20~40 mPa·s, and is suitable for high-speed coating at 50~100 m / min.